2020
DOI: 10.1590/fst.43018
|View full text |Cite
|
Sign up to set email alerts
|

Chemical composition and fatty acids profile of chocolates produced with different cocoa (Theobroma cacao L.) cultivars

Abstract: The objective of the present study was to characterize the physicochemical composition and to quantify the fatty acids of chocolates produced from different cocoa varieties (Theobroma cacao L.) cultivated in the Southern Region of Bahia. Nine samples of monovarietal chocolates were evaluated, according to their physical, thermal and fatty acid profile. The results were subjected to tests of variance and multivariate statistics. The chocolates PH16 and TSH1188 presented higher melting point. Ot was possible to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
14
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 28 publications
6
14
0
5
Order By: Relevance
“…However, the low concentration of total fat may be related to the size of the nibs particles used for fat extraction (21), and manual sample preparation may also be one of the causes of variation. The identification of 10 fatty acids was consistent with those reported by MELO et al (22), who found C14:0, C16:0, C17:0, C18:0, C18:1, C18:2, C18:3, C20:0, and C22:0 as the predominant fatty acids in chocolate. Comparably, C18:0, C18:1, and C16: 0 are the most representative fatty acids in descending order; but C16:0 and C18:0 are saturated fatty acids, which represent the largest fraction of fat in cocoa butter (23).…”
Section: Discussionsupporting
confidence: 91%
“…However, the low concentration of total fat may be related to the size of the nibs particles used for fat extraction (21), and manual sample preparation may also be one of the causes of variation. The identification of 10 fatty acids was consistent with those reported by MELO et al (22), who found C14:0, C16:0, C17:0, C18:0, C18:1, C18:2, C18:3, C20:0, and C22:0 as the predominant fatty acids in chocolate. Comparably, C18:0, C18:1, and C16: 0 are the most representative fatty acids in descending order; but C16:0 and C18:0 are saturated fatty acids, which represent the largest fraction of fat in cocoa butter (23).…”
Section: Discussionsupporting
confidence: 91%
“…Cocoa liquor contains about 55% fat. Melo et al [2020] showed the influence of the cocoa variety used in chocolate processing on the fatty acids profile, which was also confirmed in their study by Torres-Moreno et al [2015]. In addition, Mustiga et al [2019] showed the effect of genotype on the chemical composition of the beans, including the fatty acid profile.…”
Section: Fatty Acid Profiles Of the Fats Obtained From Cocoa Liquorsmentioning
confidence: 66%
“…Cocoa butter typically contains both monounsaturated and saturated FA. Palmitic acid and stearic acid (C 16:0 , C 18:0 ) are the most abundant saturated FA while oleic acid and linoleic acid (C 18:1 and C 18:2 ), are the most representative of the monounsaturated and polyunsaturated FA [36,37]. According to our results the FA identified in the chocolate analysed are: stearic acid representing the most abundant (~28%), followed by the polyunsaturated FA linoleic acid also called omega-3 (~20%), myristic acid (19%) and oleic acid (16%).…”
Section: Discussionmentioning
confidence: 99%